2005
DOI: 10.1074/jbc.m412684200
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA-directed RNA Polymerases Use Diverse Mechanisms to Promote Recombination between RNA Molecules

Abstract: An earlier developed purified cell-free system was used to explore the potential of two RNA-directed RNA polymerases (RdRps), Q␤ phage replicase and the poliovirus 3Dpol protein, to promote RNA recombination through a primer extension mechanism. The substrates of recombination were fragments of complementary strands of a Q␤ phage-derived RNA, such that if aligned at complementary 3-termini and extended using one another as a template, they would produce replicable molecules detectable as RNA colonies grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
(72 reference statements)
0
22
0
1
Order By: Relevance
“…Such studies have indicated that (i) frequent base substitutions lead to adaptations to changing environmental conditions (20), (ii) deletions as well as duplications occurring by random recombination are readily introduced into the ssRNA of leviviruses in response to various deliberate changes to the genome sequence and structure (161,192), and (iii) genomic defects can be repaired by illegitimate as well as less frequent homologous recombination occurring as a result of transesterification and template switching, respectively (47,196).…”
Section: Leviviridaementioning
confidence: 99%
“…Such studies have indicated that (i) frequent base substitutions lead to adaptations to changing environmental conditions (20), (ii) deletions as well as duplications occurring by random recombination are readily introduced into the ssRNA of leviviruses in response to various deliberate changes to the genome sequence and structure (161,192), and (iii) genomic defects can be repaired by illegitimate as well as less frequent homologous recombination occurring as a result of transesterification and template switching, respectively (47,196).…”
Section: Leviviridaementioning
confidence: 99%
“…RNA provides, for the time being, the only plausible solution to self-generation, as allowed by self-polymerization and by a variety of self-catalytic processes. Pioneering reports of RNA recombination have appeared [7][8][9][10][11][12]. With the possible exception of the systems described in [13][14][15], the reactions reported so far are not simple and robust enough to be of likely prebiotic relevance.…”
Section: Introductionmentioning
confidence: 99%
“…At low and high fitness values significant fluctuations of fitness values have been observed. This figure is based on previously published data and concepts [4, 9, 11–14, 16, 17, 19, 21, 25, 29, 31, 35, 41, 57, 5961, 66, 71, 74]. …”
Section: Introductionmentioning
confidence: 99%